2015
DOI: 10.1016/j.annemergmed.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Decisions and Delays Within Stroke Patients’ Route to the Hospital: A Qualitative Study

Abstract: Despite campaigns to increase public awareness of stroke symptoms, the behavior of both patients and health service providers apparently led to delays in the recognition of and response to stroke symptoms, potentially reducing access to optimum and timely acute specialist assessment and treatment for acute stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 31 publications
2
33
0
3
Order By: Relevance
“…If patients have no knowledge or incorrect knowledge of CVD signs and symptoms, they might be less likely to seek CVD screening or related healthcare services at an earlier stage of the disease process when these signs and symptoms first appear. (18,19) Unfortunately, these patients may only seek CVD screening services when it is too late and the CVD has reached an advanced stage where there is high morbidity and mortality. Therefore, the importance of appropriate CVD knowledge in at-risk populations also extends to signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…If patients have no knowledge or incorrect knowledge of CVD signs and symptoms, they might be less likely to seek CVD screening or related healthcare services at an earlier stage of the disease process when these signs and symptoms first appear. (18,19) Unfortunately, these patients may only seek CVD screening services when it is too late and the CVD has reached an advanced stage where there is high morbidity and mortality. Therefore, the importance of appropriate CVD knowledge in at-risk populations also extends to signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed responses were defined as those where simulated patients were not treated as an emergency and included being advised to attend an out-of-hours service or being offered an appointment with the GP the following day. Being advised to make their own way to the emergency department was also defined as a delayed response because patients can further delay attendance if they do not recognise the urgency of the situation, 17 and will not receive pre-hospital assessments and pre-notification by the EMS which are known to increase the likelihood of receiving emergency care (that is, thrombolysis) in acute stroke. 18 20 …”
Section: Methodsmentioning
confidence: 99%
“…(12)(13)(14)(15) Qualitative studies of TIA/minor stroke have predominantly focussed on patients' experiences of initial symptoms, symptom recognition and help seeking behaviour. (16)(17)(18)(19) However, some studies have explored patients' experiences after the acute stage and reported a diverse range of residual impairments, including: anxiety, (20)(21)(22)(23)(24)(25)(26) mood/emotional impact, (20,21,23,26) cognitive impairment, (21,26) fatigue, (23,25,27) physical weakness, (21,23,25) visual impairments (25) and impaired speech. (21) The impact of TIA/minor stroke on patients' ability to return to work, (25)(26)(27) performance at work, (20,25) social activities (20,21,23,26,27) and family relationships has also been reported.…”
Section: Introductionmentioning
confidence: 99%